Adsorption and dissociation of high-pressure hydrogen on Fe (100) and Fe2O3 (001) surfaces: Combining DFT calculation and statistical thermodynamics. (15th October 2022) - Li, Meifeng; Zhang, Hao; Zeng, Yimin; Liu, Jing
Abstract: Hydrogen (H2 ) pipeline systems are fundamentally the same as natural gas pipeline networks, but face a more serious safety challenge due to potential hydrogen embrittlement (HE) risk. At present, H2 transportation and storage are intentionally operated under high-pressure (HP) conditions ( i.e., 5–20 MPa for transportation, 35–100 MPa for storage), which make H2 under supercritical state ( i.e., supercritical H2, s-H2 ). In this study, the thermodynamics of H2 at a wide combination of temperatures (300–900 K) and pressures (0.1–100 MPa) has firstly been established based on a lattice-molecule model for predicting the adsorption and dissociation of gaseous and supercritical H2 on the Fe-based steel surface. The configurations of H2 adsorption and dissociation on Fe (100) and Fe2 O3 (001) surfaces were investigated through the density functional theory (DFT) calculation, and the corresponding mechanism was elucidated using hybrid orbital theory. By applying the combination of DFT calculation and statistical thermodynamics, the dissociative adsorption of HP H2 on Fe (100) and Fe2 O3 (001) surfaces upon varying temperature and pressure was predicted and the results well aligned with previously published experimental studies. Compared to the gaseous H2, s-H2 was likely to be more active on the iron (Fe) and its oxide (Fe2 O3 ) surface in terms of dissociating into H atoms and could cause steels more susceptible to HE. The results also confirmed that the presence of the Fe2 O3 scale could protect pipeline steels from environmental hydrogen permeation under the investigated HP conditions. Graphical abstract: Dissociative adsorption and free energy changes of gaseous and supercritical H2 on Fe (100) and Fe2 O3 (001) surfaces under high temperatures and pressures Image, graphical abstract